2018
DOI: 10.3892/etm.2018.5770
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of gastrodin in cell apoptosis in rat hippocampus tissue induced by desflurane

Abstract: This study investigated the protective effect ofgastrodin on cell apoptosis in rats hippocampus tissues induced by desflurane to explore its mechanism. A total of 36 rats were randomly divided into three groups: Blank control group (C group, n=12), desflurane anesthesia group (DF group, n=12) and gastrodin treatment group (GT group, n=12). Rats in DF group were treated with anesthesia using desflurane. Rats in GT group were treated with gavage using gastrodin and the same treatment as DF group. After the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Gastrodia elata, a precious treasure in traditional Chinese medicine, has been proven to be effective in the treatment of various diseases with a favorable safety profile. Gastrodin is the bioactive component of Gastrodia elata and shows high activities in sedation, blood supply improvement, anti‐inflammation, blood vessel function regulation, and neuroprotection (Liu et al, ; Wang, Wang, & Duan, ). Studies have demonstrated that placental trophoblasts in patients with preeclampsia undergo excessive apoptosis and the degree of apoptosis is related to the severity of the disease (Heazell, Buttle, & Baker, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastrodia elata, a precious treasure in traditional Chinese medicine, has been proven to be effective in the treatment of various diseases with a favorable safety profile. Gastrodin is the bioactive component of Gastrodia elata and shows high activities in sedation, blood supply improvement, anti‐inflammation, blood vessel function regulation, and neuroprotection (Liu et al, ; Wang, Wang, & Duan, ). Studies have demonstrated that placental trophoblasts in patients with preeclampsia undergo excessive apoptosis and the degree of apoptosis is related to the severity of the disease (Heazell, Buttle, & Baker, ).…”
Section: Discussionmentioning
confidence: 99%
“…By cellular immunofluorescence, the p-NF-κB (p65) was expressed in cytoplasm, the p-NF-κB (p65) protein expressions of Model group were significantly increased compared with those of NC group (p < .001, respectively, Figure 6); with gastrodin supplement, the p-NF-κB (p65) protein expressions of gastrodin-treated groups were significantly depressed compared with those of model group (p < .05, respectively, Figure 6). neuroprotection (Liu et al, 2018;Wang, Wang, & Duan, 2018). Studies have demonstrated that placental trophoblasts in patients with preeclampsia undergo excessive apoptosis and the degree of apoptosis is related to the severity of the disease (Heazell, Buttle, & Baker, 2008).…”
Section: Gastrodin Had Effects To P-nf-κb (P65) Protein Expression mentioning
confidence: 99%
“…In addition, desfl urane has been shown to induce the apoptosis mechanism, especially in neuron cells, and causes accelerated cell death. Cysteine-containing aspartate-specifi c proteases 3 (Caspase 3) and the nuclear factor-kappaB (NF-kappaB)-dependent apoptosis pathway has a very important role in the death of neurons (12,21,22). NF-kappaB is an important regulator of genes that control apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…No: YHB0616Ra; Shanghai; China). The serum IL-1β levels were duly measured according to literature (12). At the end of the procedure, the absorbance was measured with a spectrophotometer at a wavelength of 450 nm via a microplate reader.…”
Section: Biochemical Analysis Of the Blood Samplesmentioning
confidence: 99%
“…Terminal transferase-mediated biotin 2 ′ -deoxyuridine, 5 ′triphosphate nick end labeling (TUNEL) assay was performed to evaluate apoptosis of cells with a TUNEL assay kit (ab206386, Abcam, Cambridge, UK) as previously described (27). The hippocampus tissue was first deparaffinized and treated with 20 µg/ml deoxyribonuclease-free proteinase K (AM2548, Thermo Fisher Scientific, Waltham, MA, USA) at room temperature for 20 min and was then washed with PBS three times (5 min for each).…”
Section: Hematoxylin-eosin Stainingmentioning
confidence: 99%